FAKTOR-FAKTOR YANG MEMPENGARUHI LUAS PENGUNGKAPAN SUKARELA DALAM ANNUAL REPORT - Noor Laila Fitriana; Andri Prastiwi (Diponegoro Journal of Accounting, 2014)
This study aims to analyze the factors that affect the wider voluntary disclosure. Voluntary disclosure is needed by investors and other users in making better decisions because it is considered mandatory disclosure is not sufficient in providing information to investors. The factors examined in this study are firm size, leverage, profitability, firm age, size of the firm, and the proportion of independent board. The sample of this study are secondary data from the Indonesia Stock Exchange in the form of annual reports companies listed in 2010-2012. Determination of the sample using purposive sampling method with judgment sampling technique. The total sample in this study was 49 companies. This study uses multiple regression analysis. This is because the variables are tested more than one independent variable. The results show that profitability, size of the firm, and the proportion of independent board broad positive effect on voluntary disclosure, while negatively affects leverage extensive voluntary disclosure. Meanwhile, firm size and firm age has no effect on the wider voluntary disclosure.